Occurrence of roquefortine C, mycophenolic acid and aflatoxin M1 mycotoxins in blue-veined cheeses. (January 2015) - Fontaine, Kévin; Passeró, Elena; Vallone, Lisa; Hymery, Nolwenn; Coton, Monika; Jany, Jean-Luc; Mounier, Jérôme; Coton, Emmanuel
Abstract: Penicillium roqueforti, a food and feed contaminant, is known for its potential to produce roquefortine C (ROQC) and mycophenolic acid (MPA) amongst other mycotoxins. In blue-veined cheeses, selected P. roqueforti ripening cultures are used for organoleptic development but little is known about mycotoxin occurrence in these products. In this study, aflatoxin M1 (AFM1), ROQC and MPA levels were determined in 86 blue-veined cheeses collected worldwide using liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). AFM1 was absent in all samples while 97.7% and 37.2% of cheeses contained quantifiable ROQC and MPA levels, respectively. Overall, the analyzed cheeses contained a large range of mycotoxin concentrations with ROQC and MPA mean levels at 848 ± 1670 μg/kg and 841 ± 1271 μg/kg, respectively. Noteworthy, 75% of cheese samples contained less than 792 μg/kg ROQC and 705 μg/kg MPA. Highlights: Mycotoxin analysis of an unprecedented worldwide blue-veined cheese collection. AFM1 was absent in all samples. High variability of ROQC and MPA contamination was observed. Overall, 75% of cheese samples contained less than 792 μg/kg ROQC and 705 μg/kg MPA.